Evidence for communication of peripheral iron status to cerebrospinal fluid: clinical implications for therapeutic strategy - James R. Connor; Kari Duck; Stephanie Patton; Ian A. Simpson; Lynn Marie Trotti; Richard Allen; Christopher J. Earley; David Rye (Fluids and Barriers of the CNS, 2020)
Abstract Background Iron is crucial for proper functioning of all organs including the brain. Deficiencies and excess of iron are common and contribute to substantial morbidity and mortality. Whereas iron’s involvement in erythropoiesis drives clinical practice, the guidelines informing interventional strategies for iron repletion in neurological disorders are poorly defined. The objective of this study was to determine if peripheral iron status is communicated to the brain. Methods We used a bi-chamber cell culture model of the blood–brain-barrier to determine transcytosis of iron delivered by transferrin as a metric of iron transport. In the apical chamber (representative of the blood) we placed transferrin complexed with iron59 and in the basal chamber (representative of the brain) we placed human cerebrospinal fluid. Cerebrospinal fluid (CSF) samples (N = 24) were collected via lumbar puncture. The integrity of the tight junctions were monitored throughout the experiments using RITC-Dextran. Results We demonstrate that iron transport correlates positively with plasma hemoglobin concentrations but not serum ferritin levels. Conclusions The clinical ramifications of these findings are several- fold. They suggest that erythropoietic demands for iron take precedence over brain requirements, and that the metric traditionally considered to be the most specific test reflecting total body iron stores and relied upon to inform treatment decisions–i.e., serum ferritin–may not be the preferred peripheral indicator when attempting to promote brain iron uptake. The future direction of this line of investigation is to identify the factor(s) in the CSF that influence iron transport at the level of the BBB.